2021
DOI: 10.1186/s40170-021-00260-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide promotes metastasis via acceleration of glycolysis by the nuclear factor-κB/snail/hexokinase3 signaling axis in colorectal cancer

Abstract: Background Cancer cell is generally characterized by enhanced glycolysis. Inflammasome activation is interaction with glycolysis. The concentration of lipopolysaccharide (LPS), a classic inflammasome activator, is significantly higher in colorectal cancer tissue than in normal intestinal mucosa. However, the mechanism of LPS on glycolysis and metastasis has not been fully elucidated. This study aimed to investigate the roles of LPS on inflammasome activation, glycolysis, and metastasis, and unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…al (2013) (33) they reported the oxidative stress and apoptosis inducing properties of LPS. It also been reported for promoting metastasis in cancer cells (34), (32). In this study, similar result with Halawa et.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…al (2013) (33) they reported the oxidative stress and apoptosis inducing properties of LPS. It also been reported for promoting metastasis in cancer cells (34), (32). In this study, similar result with Halawa et.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study antioxidative efficacy of OIM was tested in a LPS stimulated immunecompromise model of murine splenic macrophages. LPS a cellular component of gram negative bacteria is a classic inflammasome activator (32). In recent study, of Halawa et.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is a gram-negative bacterial antigen that activates TLR4 and induces immunosuppressive factors and apoptosis resistance, thereby promoting immune escape in human CRC cells ( Li et al, 2014 ). Wu et al have found that LPS accelerates glycolysis through the nuclear factor-κB/snail/hexokinase3 signaling axis to promote CRC metastasis ( Wu et al, 2021a ), and Liu et al have found that activation of p38 mitogen-activated protein kinase pathway by LPS aggravates postoperative intestinal obstruction in CRC patients ( Liu et al, 2022 ). Collectively, LPS might play an important role in the progression of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin can inhibit the proliferation, invasion, and survival and induce apoptosis of ovarian, pancreatic, breast, and colonic CSCs and prevent cancer recurrence and spread [ 131 - 134 ]. Fifth, metformin has been reported to inhibit the activity of the transcription factor NF-κB, leading to reduced secretion of proinflammatory cytokinesthat may have tumorigenic effects [ 135 ].…”
Section: Metformin and Cancermentioning
confidence: 99%